Genome-wide identification, comprehensive characterization of transcription factors, cis-regulatory elements, protein homology, and protein interaction network of DREB gene family in Solanum lycopersicum - Maqsood, Hajra; Munir, Faiza; Amir, Rabia; Gul, Alvina (Frontiers in Plant Science, 2022)
Tomato is a drought sensitive crop having high susceptibility to adverse climatic changes. Dehydration responsive element binding (DREB) are significant plant transcription factors (TFs) that have a vital role in regulating plant abiotic stress tolerance; by networking with DRE/CRT cis-regulatory elements in response to stresses. In this study, bioinformatics analysis was performed to conduct the genome-wide identification and characterization of DREB genes and promoter elements in Solanum lycopersicum. In genome wide coverage 58 SlDREB genes were discovered on 12 chromosomes that justified the criteria of the presence of AP2 domain as conserved motifs. Intron-exon organization and motif analysis showed consistency with phylogenetic analysis and confirmed the absence of the A3 class, thus divided SlDREB genes into five categories. Gene expansion was observed through tandem duplication and segmental duplication gene events in SlDREB genes. Ka/Ks values were calculated in orthologue pairs that indicated divergence time and occurrence of purification selection during the evolutionary period. Synteny analysis demonstrated that 32 out of 58 and 47 out of 58 SlDREB genes were orthologues to Arabidopsis and Solanum tuberosum respectively. Subcellular localization predicted that SlDREB genes were present in nucleus and performed primary functions in DNA binding to regulate the transcriptional processes according to gene ontology. Cis-acting regulatory element analysis revealed the presence of 103 motifs in 2.5kbp upstream promotor sequences of 58 SlDREB genes. Five representative SlDREB proteins were selected from the resultant DREB subgroups for 3D protein modelling through the Phyre2 server. All models confirmed about 90% residues in the favourable region through Ramachandran plot analysis. Moreover, active catalytic sites and occurrence in disorder regions indicated the structural and functional flexibility of SlDREB proteins. Protein association networks through STRING software suggested the potential interactors that belong to different gene families and are involved in regulating similar functional and biological processes. Transcriptome data analysis has revealed that SlDREB gene family is engaged in defense response against drought and heat stress conditions in tomato. Overall, this comprehensive research reveals the identification and characterization of SlDREB genes that provide potential knowledge for improving abiotic stress tolerance in tomato.